2010
DOI: 10.1021/jp100341h
|View full text |Cite
|
Sign up to set email alerts
|

Directed Growth and Microwave Absorption Property of Crossed ZnO Netlike Micro-/Nanostructures

Abstract: Three-dimensional ZnO micro/nanorod networks were synthesized through the direct evaporation of metal zinc and graphite powders in Ar and O 2 at 910 °C without any catalyst. The micro/nanorod networks of as-synthesized ZnO were characterized by using scanning electron microscopy, high-resolution transmission electron microscopy, and X-ray diffraction. The branches within one network show very regular cross orientation. The nanorods follow a growth direction [0001]. Mircrowave absorption properties of the ZnO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(76 citation statements)
references
References 20 publications
(37 reference statements)
0
74
0
1
Order By: Relevance
“…13 (Li et al, 2010). It can be seen that CNTs and T-ZnO nanostructures concentration has an obvious effect on microwave absorption properties.…”
Section: Microwave Absorption Properties Of T-zno Plus Cnts / Ep Coatmentioning
confidence: 95%
See 1 more Smart Citation
“…13 (Li et al, 2010). It can be seen that CNTs and T-ZnO nanostructures concentration has an obvious effect on microwave absorption properties.…”
Section: Microwave Absorption Properties Of T-zno Plus Cnts / Ep Coatmentioning
confidence: 95%
“…Also, the Fig. 5b indicates the ZnO microrods with a rough surface, possibly due to the competition between surface energy and strain energy (Li et al, 2010).…”
Section: Fabrication Of Three-dimensional Zno Networkmentioning
confidence: 99%
“…The uniform coating of Ni nanoparticles considerably enhances the interfacial polarization, dielectric properties, and magnetic loss of ZnO@Ni; hence, the MA properties of this material are remarkably improved. Zhang et al 25 have reported that ZnO net-like micro/nanostructures/para±n composites present a high performance in MA. Liu et al 26 reported that ZnO@MWCNTs show a re°ection coe±cient of approximately À20 dB at room temperature; this nding indicates that ZnO induces a synergistic e®ect in enhancing MA.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In order to further improve the microwave absorption performance of ZnO, scientists have made much e®orts and their interest is mainly focused on the two aspects. On the one hand, ZnO with unique microstructure is fabricated, such as tetra-needlelike ZnO whiskers, 6 ZnO nanorods, 9 ZnO nanotrees, 14 ZnO dendritic nanostructures, 15 nanoneedlelike ZnO, 16 crossed ZnO netlike micro-/nanostructures, 17 etc. For example, Liu et al fabricated nanoneedlelike ZnO via a facile combustion synthesis route and the materials exhibited enhanced permittivity and multi-region microwave absorption in the X-band at elevated temperature and the minimum re°ection loss (RL min ) reached À44 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The value of RL min for the composites with 50 vol.% ZnO netlike structures was À37 dB at 6.2 GHz with a thickness of 4.0 mm. 17 On the other hand, ZnO is complexed or hybridized with other components to fabricate composites, such as ZnO/reduced graphene oxide (ZnO/ RGO), 4,18,19 ZnO/multi-wall carbon nanotubes (ZnO/MWCNTs), 5,20 ZnO/Fe 3 O 4 composites 21,22 etc. For instance, Wu et al fabricated 3D ZnO/ RGO nanocomposites using a two-step reduction process and found that the composites exhibited excellent microwave absorbing properties, i.e., the maximum e®ective absorption bandwidth of RL lower than À10 dB could reach 6.4 GHz when thē ller loading was 10 wt.% and the thickness of the absorber was 2.5 mm.…”
Section: Introductionmentioning
confidence: 99%